PENINGKATAN KREATIVITAS SISWA KELAS 4 SD MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) - Renny Setyowati; Romirio Torang Purba (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
This study aims to improve the creativity of science students learning grade 4 SDN Jatirunggo 02 Pringapus through learning models Contextual Teaching And Learning (CTL). This research is a classroom action research (PTK) using spiral model from Stephen Kemmis and Robin Mc Taggart which is done in two cycles. The subjects of this study were 4 grade students of SDN Jatirunggo 02 Pringapus, consisting of 33 students, ie 13 male students and 20 female students. Technique of collecting data in the form of observation technique. Data analysis technique used is descriptive comparative. The results show that the creativity of fourth grade students can be improved through CTL Learning Model. Keywords: Creativity, Contextual Teaching And Learning (CTL)